2019
DOI: 10.3126/njb.v7i1.26945
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Patterns and Plasmid Profiles of Methicillin Resistant Staphylococcus aureus Isolated from Clinical Samples

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA), showing resistance to several antibiotics is a global health problem associated with considerable mortality and morbidity. Antibiotic susceptibility test is a commonly used method to characterize MRSA in epidemiologic studies. Additionally, plasmid profile has been reported to be useful in tracing the epidemiology of antibiotic resistance. This research was conducted to determine the antimicrobial resistance patterns and plasmid profiles of MRSA isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Multiple studies indicate that MRSA is a serious threat to hospitalized patients globally and it now represents a challenge for public health, as communityassociated infections appear to be on the increase in both adults and children in different regions and countries. 25 Available studies suggest that the prevalence rate of MRSA in other regions of the country was not uniform, and a significant variation in its prevalence has been documented in different settings throughout the world. This study revealed a prevalence of 78.01% MRSA, which was higher than previous studies conducted in other regions, including 25.4% in China, 5 and 36.69% in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that MRSA is a serious threat to hospitalized patients globally and it now represents a challenge for public health, as communityassociated infections appear to be on the increase in both adults and children in different regions and countries. 25 Available studies suggest that the prevalence rate of MRSA in other regions of the country was not uniform, and a significant variation in its prevalence has been documented in different settings throughout the world. This study revealed a prevalence of 78.01% MRSA, which was higher than previous studies conducted in other regions, including 25.4% in China, 5 and 36.69% in Nepal.…”
Section: Discussionmentioning
confidence: 99%